2010
DOI: 10.1590/s1984-70332010000300001
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis performance in industrial and yield components of sweet corn

Abstract: -Heterosis and its components were evaluated in a diallel crossing system of sweet corn. In the 38 treatments, eigth parents, 28 hybrids and two controls were used, arranged in a randomized block design with three replications.The diallel analysis followed the methodology of Gardner and Eberhart (1966

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
1
8
1
2
Order By: Relevance
“…Assunção et al (2010), evaluating sweet corn cultivars, found ĥ i estimates of AE ranging from -1.889 to 1.556 days, which are lower values than those found in this study.…”
Section: Resultscontrasting
confidence: 96%
See 1 more Smart Citation
“…Assunção et al (2010), evaluating sweet corn cultivars, found ĥ i estimates of AE ranging from -1.889 to 1.556 days, which are lower values than those found in this study.…”
Section: Resultscontrasting
confidence: 96%
“…Moreover, diallel crosses are used to analyze the genetic design, providing estimates of useful parameters that allow for the selection of the best genitors to obtain hybrids, and to understand the genetic effects of a trait (Gonçalves et al, 2014;Melani & Carena 2005;Cruz, Regazzi, & Carneiro, 2004). This method has been used to evaluate several agronomic traits in hybrids obtained from common maize populations (Tonette & Carena, 2014;Bernini, & Paterniani, 2012;Doná, Paterniani, Gallo, & Duarte, 2011) and in specialty corns, such as popcorn (Cabral et al, 2015;Solalinde et al, 2014) and sweet corn (Assunção et al, 2010;Rodrigues et al, 2009), allowing the identification of the best parents and their hybrid combinations for the evaluated traits. Cruz et al (2004) reported several types of diallel analysis, such as balanced, partial, circulating, incomplete and unbalanced, highlighting that the most applicable type was the balanced diallel proposed by Hayman (1954), Griffing (1956) and Gardner and Eberhart (1966).…”
Section: Introductionmentioning
confidence: 99%
“…The traits YIELD and NEP are considered the most important to evaluate the agronomic performance of super-sweet corn (Butrón et al 2008, Assunção et al 2010, Revilla et al 2010. Since no interaction with the location was detected for these traits, it is possible to recommend superior genotypes for the locations where they were tested.…”
Section: Resultsmentioning
confidence: 99%
“…The negative h ̅ value indicates bidirectional dominance, with the occurrence of positive and negative heterosis (Assunção et al, 2010).…”
Section: Effects Of Average Variety and Specific Heterosismentioning
confidence: 99%
“…Miranda Filho and Geraldi (1984) adapted the model of Gardner and Eberhart (1966) to estimate heterotic effects in partial diallel crosses. Using the methodology of Gardner and Eberhart (1966) of diallel crosses, Assunção et al (2010) identified positive heterosis for the majority of the traits of agronomic interest and of grain quality in sweet corn. Nevertheless, no studies utilizing this methodology for elephant grass have been found.…”
Section: Introductionmentioning
confidence: 99%